Home Security System by Three Methods Using Arduino Nano Based PV Energy Source - Mungkin, Moranain; Sijabat, Tonggo; Bahri, Zulkifli; Satria, Habib; Siregar, Muhammad Fadlan; Dayana, Indri (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The existence of technology today aims to help make human work easier, including in the aspect of residential security systems. The increase in crime, especially theft in residential homes, is increasingly worrying. Therefore, the application of Arduino Nano control system technology with other supporting systems is the right solution to improve the safety of residents and minimize theft. This research aims to design a device called Home Security System by Three Methods that uses PV energy sources and the Arduino Nano control system. This tool features three security methods: SMS gateway, phone call, and alarm sound in two locations. Tests were carried out by simulating the opening and closing of doors/windows, then paying attention to the system response on the smartphone and the two alarms. The test results show that when a door/window is opened, the system sends an alert SMS to the user's smartphone within ± 9 seconds. The alarm sounds inside the house and the security post. If the user does not respond, the system will make a phone call within ± 55 seconds after the door/window is opened. The system works based on the movement or gap in the door/window using a magnetic switch sensor of ± 2.5 cm.